Utilizing Cake Application in Teaching Speaking to High School Students in Indonesia - Desmayanti, Fitria; Romadlon, Farid Noor; Rusiana, Rusiana (Universitas Muria Kudus, 2024)
Many high school students still struggle with speaking, especially pronunciation and word choice that reflects their intended meaning. The study aims to know the effectiveness of using the Cake application to teach speaking skills. This research used a quantitative method and used a pre-experimental design. The sample consists of 35 students from XI F 6 of SMA 2 Bae Kudus. The research used a speaking test as the research data. The result of this study revealed the average value of the pre-test was 34.6, while the average value of the post-test was 49.5. The result of the analysis from SPSS revealed the value of Sig. (2-tailed) 0.00 0.05. If the value has a significance value (p-value) of 0.00, which is smaller than 0.05, then this indicates that the difference between the pre-test and post-test is highly significant. Therefore, the Cake application is effective in teaching speaking skills. Future research might consider the length of the research treatment and according to the material of the subject year.